Planned material irradiation capabilities of IFMIF-DONES. (August 2018) - Arbeiter, Frederik; Diegele, Eberhard; Fischer, Ulrich; Garcia, Angela; Ibarra, Angel; Molla, Joaquin; Mota, Fernando; Möslang, Anton; Qiu, Yuefeng; Serrano, Marta; Schwab, Florian
Highlights: Irradiation conditions for steel match the conditions anticipated for DEMO. Accelerated testing for steel is possible in IFMIF-DONES. Accelerated testing for tungsten and copper is possible in IFMIF-DONES. Testing of tungsten is possible at up to 800 °C. Abstract: IFMIF-DONES (International Fusion Materials Irradiation Facility - DEMO-oriented Neutron Source) is currently being developed in the frame of the EUROfusion Early Neutron Source work package (WPENS), based on the results achieved in the ongoing IFMIF/EVEDA (Engineering Validation and Engineering Design Activities) project by Japan and Europe in the frame of the Braoder Approach (BA) agreement. The neutron source's limited product of "irradiation volume × neutron fluence" on one hand and the large potential test matrix (defined by number of material grades, test types, irradiation- and test temperature levels and damage dose levels) on the other hand, require a careful selection of test conditions by collaborative effort of the communities of DEMO designers, fusion materials science and the irradiation facility designers. This paper describes achievable irradiation conditions in the High Flux Test Module (HFTM) of IFMIF-DONES, characterized by levels and gradients of irradiation temperatures and nuclear responses (dpa, H and He production). The HFTM development focuses on 9%-Cr Reduced Activation Ferritic Martensitic steel irradiations, but also the possibilities of tungsten and copper alloy irradiations are explored. Possible specimen arrangements and issues of the Small Specimens Test Technique are also discussed.